2018
DOI: 10.11648/j.ijgg.20180603.11
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Nucleotide Changes in Cataract and Glaucoma Patients in Senegal

Abstract: Cataract and glaucoma are the leading causes of blindness in the world. The aim of this study was to investigate the involvement of somatic mutations of the MT-CYB gene in glaucoma and cataract cases among Senegalese patients. 38 samples including 12 controls and 26 patients (18 cataracts, 8 glaucomas) were used to study polymorphism, diversity and genetic structuration of the MT-CYB gene. DNA was isolated from whole blood samples and then the gene was genotyped by PCR-Sequencing. The study of the chromatogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Moreover, a pathogenic synonymous variant G4580A ( ND2 ) in PCG[ 9 10 ] a pathogenic deletion G4821del ( ND2 ) in POAG[ 10 ] and a pathogenic insertion T15684TA in glaucoma had also been reported. [ 21 ] In addition, a NS pathogenic variant C5178A ( ND2 ) was found common in two studies on Indian and Korean population[ 8 24 ] Apart from this, pathogenic variants have also been reported in RNA regions of POAG patients viz. A1453G in 12S rRNA, A1892G and A2755G in 16S rRNA and C3254T, T4336C, T4363C, C7471T, A15909G in tRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a pathogenic synonymous variant G4580A ( ND2 ) in PCG[ 9 10 ] a pathogenic deletion G4821del ( ND2 ) in POAG[ 10 ] and a pathogenic insertion T15684TA in glaucoma had also been reported. [ 21 ] In addition, a NS pathogenic variant C5178A ( ND2 ) was found common in two studies on Indian and Korean population[ 8 24 ] Apart from this, pathogenic variants have also been reported in RNA regions of POAG patients viz. A1453G in 12S rRNA, A1892G and A2755G in 16S rRNA and C3254T, T4336C, T4363C, C7471T, A15909G in tRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ba et al . [ 21 ] investigated the involvement of somatic mutations of the MT-CYB gene in 8 Senegalese glaucoma patients and 12 controls. The study found a pathogenic insertion specific for glaucoma at position m. T15684TA and concluded that MT-CYB somatic mutations are involved in the occurrence of glaucoma in Senegalese.…”
Section: Mitochondrial Dna Variations and Glaucomamentioning
confidence: 99%